Analisis Kesulitan Pembelajaran Kitab Fiqih: Studi Kasus di Pondok Pesantren Hidayatul Qur’an Batanghari Lampung Timur - Suseno, Nugroho Noto; Irwansyah, Dedi; Syukron, Buyung; Ardiyansyah, Ahmad; Fitriyah, Fitriyah (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to (1) identify the various difficulties experienced by students in learning the Fiqh Book, and (2) analyze the factors causing these difficulties and the efforts made by the council of ustadz in teaching the Fiqh Book (Mabādi’ul Fiqhiyyah) at the Hidayatul Qur'an Islamic Boarding School, Batanghari, East Lampung. This study uses a qualitative approach with a case study method as a type of field study. The study results indicate that students experience difficulties in learning the Fiqh Book in terms of reading Arabic texts, understanding the material, and low interest and motivation to learn. This failure is caused by internal factors such as physical and psychological conditions, learning styles and attitudes, and lack of concentration; external factors such as educational background, teaching methods, and social interaction. The efforts of the ustadz in overcoming this include providing additional lessons, enriching Arabic language understanding, practicing reading bare and pegon Arabic texts, personal motivation, and periodic learning evaluations. In addition, the active involvement of students in the learning process also contributes to overcoming learning obstacles. Students actively asking questions, discussing, and showing learning initiatives tend to experience increased understanding. The implications of this study emphasize the importance of synergy between the teaching strategies of the ustadz and the active participation of the students in creating an effective Fiqh learning process in the Islamic boarding school environment.